The Drosophila Cadherin Fat regulates tissue size and planar cell polarity through different domains. - Xuesong Zhao (Public Library of Science (PLoS), 2013)
The Drosophila Cadherin Fat (Ft) has been identified as a crucial regulator of tissue size and Planar Cell Polarity (PCP). However, the precise mechanism by which Ft regulates these processes remains unclear. In order to advance our understanding of the action of Ft, we have sought to identify the crucial Ft effector domains. Here we report that a small region of the Ft cytoplasmic domain (H2 region) is both necessary and sufficient, when membrane localized, to support viability and prevent tissue overgrowth. Interestingly, the H2 region is dispensable for regulating PCP signaling, whereas the mutant Ft lacking the H2 region is fully capable of directing PCP. This result suggests that Ft's roles in PCP signaling and tissue size control are separable, and each can be carried out independently. Surprisingly, the crucial regions of Ft identified in our structure-function study do not overlap with the previously reported interaction regions with Atrophin, Dco, or Lowfat.